Overexpression of BpAP1 induces early flowering and produces dwarfism in Betula platyphylla × Betula pendula. Issue 4 (29th January 2014) - Huang, Haijiao; Wang, Shan; Jiang, Jing; Liu, Guifeng; Li, Huiyu; Chen, Su; Xu, Huanwen
<x xml:space="preserve">Abstract</x> The involvement of APETALA1 (AP1) in the flowering transition has been the focus of much research. Here, we produced Betula platyphylla × Betula pendula (birch) lines that overexpressed BpAP1 using Agrobacterium‐mediated transformation; we obtained five independent 35S::BpAP1 transgenic lines. Polymerase chain reaction (PCR), Southern, northern and western analyses were used to identify the transformants. As determined by quantitative real‐time PCR (qRT‐PCR), BpAP1 expression in roots, shoots, leaves and terminal buds of 35S::BpAP1 transgenic lines was significantly higher than that in the wild type (WT, P < 0.01). The average height of 2‐year‐old 35S::BpAP1 plants was significantly lower (41.17%) than that of non‐transgenic plants. In the 35S::BpAP1 lines, inflorescences emerged successively beginning 2 months after transplanting. In addition, the length–diameter ratio of fully developed male and female inflorescences were both significantly less than those of the WT (P < 0.05), i.e. the morphological characteristic was stubby. The male inflorescences emerged early, with empty, draped anthers, and pollen was rarely produced, whereas the female floret structure was not different from WT. The pistils developed normally and could accept pollen, leading to the production of hybrid progeny (F1). F1 plants completed flowering within only 1 year after sowing. We demonstrate that BpAP1 can be inherited through sexual reproduction. Overexpression of BpAP1 caused early flowering and dwarfism; these lines had an obviously shortened juvenile phase. These results greatly increase our understanding of the mechanisms underlying the flowering transition and enhance genetic studies of birch traits, and they open up new possibilities for the breeding of birch and other woody plants.